Is the identification of caseating granuloma in the intestine indicative of tuberculosis? a rare case of Crohn’s disease - Siqi Tao; Yan Chen; Wen Hu; Keren Shen; Jinghong Xu (Diagnostic Pathology)
Abstract Background Crohn’s disease (CD) is a chronic intestinal inflammatory disorder, the etiology of which remains unknown, and is characterized by symptoms such as chronic abdominal pain, diarrhea, obstruction, and perianal lesions. Histopathology is widely regarded as the preferred method for diagnosing CD, although the histological diagnosis may lack specificity. The identification of granulomas is commonly believed to be the most reliable diagnostic indicator for CD, surpassing all other clinical features in significance. Nevertheless, research indicates that the detection rate of granulomas in CD exhibits considerable variability. Furthermore, granulomas can manifest in various specific infections including tuberculosis and Yersinia, as well as in a range of diseases characterized by macrophage reactions such as sarcoidosis and drug-induced enteritis. Granulomas associated with CD typically do not exhibit necrosis. However, the formation of caseous granulomas may occur as a result of secondary infections related to anti-CD drug treatment or perforation of the intestinal wall. Case presentation In this study, we present a case of a 28-year-old female patient diagnosed with CD exhibiting histologic granulomas, including both caseating and non-caseating forms, which demonstrated a positive response to medical treatment. Conclusion In clinical practice, various forms of granulomas may indicate diverse underlying diseases, yet lack specificity. It is suggested that the presence of caseous granulomas should not be considered as a definitive exclusion criterion for the diagnosis when clinical, endoscopic, imaging and other histopathological features are consistent with CD. This study is the first report of caseous granulomas in CD without concomitant tuberculosis infection.